Travelling and embedded policy: The case of knowledge transfer - Ozga, J; Jones, R (2006)
Knowledge transfer (KT) has entered the higher education arena in the UK as the 'third sector of higher education activity - along with research and teaching. Its antecedents lie in the commercialization and technology transfer of the late 1980s and 1990s, and this business-like orientation remains dominant in the KT policy discourse. This paper explores the extent to which policy for KT may be understood both as 'travelling policy shaped by globalizing trends in pursuit of successful competition in the new knowledge economy (KE) and as 'embedded policy mediated by local contextual factors that may translate policy to reflect local priorities and meanings. In considering evidence of 'embedded policy the paper develops its arguments through preliminary analysis of KT policy in Scotland where - at least at the level of discourse - there is an attempt in post-devolution Scotland to encourage KT in the broader public interest. However, KTs antecedents may continue to shape the engagement of academic staff in Scotland, as may the wider context of UK policy steering in higher education.